Fighting Westway : environmental law, citizen activism, and the regulatory war that transformed New York City - Buzbee, William W., 1960- (Cornell University Press, 2014)
From 1971 to 1985, battles raged over Westway, a multibillion-dollar highway, development, and park project slated for placement in New York City. It would have projected far into the Hudson River, including massive new landfill extending several miles along Manhattan's Lower West Side. The most expensive highway project ever proposed, Westway also provoked one of the highest stakes legal battles of its day. In Fighting Westway, William W. Buzbee reveals how environmentalists, citizens, their lawyers, and a growing opposition coalition, despite enormous resource disparities, were able to defeat this project supported by presidents, senators, governors, and mayors, much of the business community, and most unions. Although Westway's defeat has been derided as lacking justification, Westway's critics raised substantial and ultimately decisive objections. They questioned claimed project benefits and advocated trading federal Westway dollars for mass transit improvements. They also exposed illegally disregarded environmental risks, especially to increasingly scarce East Coast young striped bass often found in extraordinarily high numbers right where Westway was to be built. Drawing on archival records and interviews, Buzbee goes beyond the veneer of government actions and court rulings to illuminate the stakes, political pressures, and strategic moves and countermoves that shaped the Westway war, a fight involving all levels and branches of government, scientific conflict, strategic citizen action, and hearings, trials, and appeals in federal court. This Westway history illuminates how high-stakes regulatory battles are fought, the strategies and power of America's environmental laws, ways urban priorities are contested, the clout of savvy citizen activists and effective lawyers, and how separation of powers and federalism frameworks structure legal and political conflict. Whether readers seek an exciting tale of environmental, political, and legal conflict, to learn what really happened during these battles that transformed New York City, or to understand how modern legal frameworks shape high stakes regulatory wars, Fighting Westway will provide a good read.